Avaliação de desempenho de olanzapina e risperidona em pacientes com esquizofrenia no Sistema Único de Saúde: estudo de efetividade em uma coorte de dezesseis anos no Brasil. - Wallace Breno Barbosa (2021)
Introduction: Antipsychotics have stood out in the treatment of patients with schizophrenia and some of these drugs are provided by SUS. The challenge of understanding the efficacy, effectiveness and safety of these drugs remains in evidence. Objective: To evaluate the real-world effectiveness and its associated factors of olanzapine and risperidone in the treatment of patients with schizophrenia, through a cohort of 16 years of follow-up and nationwide. Methods: Three SUS databases were integrated and paired: Outpatient, Hospital and Mortality Information Systems. Subsequently, the patients were paired (1:1) for psychiatric hospitalization, year of receipt of the antipsychotic, sex and age; according to the cohort entry medications, olanzapine or risperidone. The cumulative probability curves of treatment discontinuation, generated by the Kaplan-Meier estimator, were analyzed and the factors associated with psychiatric hospitalization or death were evaluated using Cox's proportional hazards model. Subsequently, multivariate and sensitivity analyzes were performed. Results: 3416 pairs of patients were included, 1708 in the olanzapine group and 1708 in risperidone. Olanzapine had a longer time until discontinuation of treatment (p = 0.021). Consequently, risperidone was at higher risk for treatment discontinuation of treatment (p = 0.021), including in the multivariate analysis (p = 0.017). Considering the psychiatric hospitalization event, the risk was also greater with risperidone (p = 0.006). Among patients persisting for 24 months, there were no statistically significant differences between olanzapine and risperidone for the risk of discontinuation of treatment (p = 0.06). Conclusions: Olanzapine was shown to be more real world effective than risperidone, considering the entire population and among patients who had psychiatric hospitalization as an event. These findings were not supported in all analyzes. Possibly, patients in this cohort are being followed up on an outpatient basis and are more stable. Real-world studies from large databases collaborate with experimental studies in consolidating evidence.